Stability of the General Mixed Additive and Quadratic Functional Equation in Quasi Banach Spaces: Prondanai Kaskasem, Chakkrid Klin-eam, Boriwat Noytabtim - Team, Support (Thai Journal of Mathematics, 2020)
In this paper, we prove the generalized Hyers-Ulam-Rassias stability of the following general mixed additive and quadratic functional equation f(λ x +y) +f(λ x -y) =f(x+y)+f(x-y)+(λ -1)[(λ +2)f(x)+λ f(-x)] where λ N and λ eq 1 in quasi Banach spaces. Moreover, we use contractive subadditive and expansively superadditive function to prove stability of the general mixed additive and quadratic functional equation in quasi Banach spaces.